(untitled) - Hoyt, Edwin P. (Tokyo, Japan, 1993)
Japan's military traditional underwent the same transformation at the end of the nineteenth century as the rest of that country's institutions in its rush to modernize and emulute the West. From the victory of Admiral Togo against the Russian Fleet, to Yamamoto's surprise attack on Pearl Harbor and yamashita's unthinkable land-based conquest of Singapore, Japanese feats of arm amazed the world.